Exigência de energia e proteína para mantença estimada por restrição quantitativa de alimento para Tilápia do Nilo em dois sistemas de produção - Tulio Soares de Brito (2017)
Feeding rates (TA) are one of the main management tools, since that the adjusting the nutrient may intake increases its efficiency and reduces the environmental impact. Protein and energy requirements, and their respective retention efficiencies (Kp and Ke) are determining factors for the adjustment of TA. The addition of carbon (MAC) is a tool that can determine higher productivity of a biofloc system (BFT). The carbon addition plan (MAC) can determine higher productivity of a biofloc system (BFT). The objective of the study was to estimate the protein and energy requirements for maintenance and growth by the factorial method for Niletilapia Oreochromis niloticus, the most efficient TA and MAC and the risk factors involved in the cultivation of in BFT. In the nutritional requirement assay, the quantitative feed restriction method was used, with four TA (1, 0.75, 0.5 and 0.25). The experiment was split into two subsequent phases (P1 with duration of 39 days and P2 with duration of 58 days), to verify the behavior of the responses evaluated during growth. The efficiency of energy utilization for protein and lipid deposition (KP and KL) and energy requirement for maintenance was calculated using the factorial model. In the BFT assay, the same TA and two subsequent MAC were used. A constant addition of molasses (carbon source) was used in MAC 1 to raise the ratio of C:N to 1:17, as a function of the protein added as feed and MAC 2 was performed as a function of ammonia concentration (NH3) in water, in the proportion of 6 g of molasses to 1 g of NH3. Nitrite (NO2), alkalinity, pH, total dissolved solids estimated by electrical conductivity (SDTe), sedimentable solids volume (VSS) were evaluated during of the 99 days of growth trial. The interactions between TA and MAC on water quality and growth were made through linear mixed effects models and the Cox's model of proportional hazards to determine the risk factors associated with mortality. The requirement for metabolizable energy for maintenance estimated was 11 kcal kg-0.8. The KP was 0.25 and the KL was 0.88. The digestible protein requirement for maintenance was 0.65 g kg-0.7 day -1 and the theoretical maximum protein deposition capacity was 0.99 g kg-0.7 day -1. At BFT trial there was a strong impact of the water quality variables on the performance of the animals, VSS, TDSe and pH were affected by TA and MAC. TDSe was the main risk factor that contributed to the occurrence of mortality. Growth was favored with MAC 2 and feed efficiency optimized with TA corresponding to 1.3% of body weight (TA 0.75).